Repertorium der griechischen und lateinischen Inschriften aus Mysien - Stauber, Josef (Denkschriften (Österreichische Akademie der Wissenschaften. Philosophisch-Historische Klasse), 2022)
The 2170 inscriptions from this region of north-western Asia Minor reveal everyday life, celebrations, private worship, state cults, local organisation and international politics from the 6th century BC to the 6th century AD. The inscriptions have been collected from publications which are often hard to access; many of the stones are now lost. The two volumes offer the Greek and Latin inscriptions with translation, commentary, bibliographical references, and 1550 figures. Indices will be published in a third volume.